Ultrasound-Guided Scalp Block as an Anesthetic Technique and Postoperative Analgesia for Awake Cranioplasty in High-Risk Patients - Prihatno, M. Mukhlis Rudi; Wicaksono, Nugroho; Luailiyah, Afridatul (Jurnal Neuroanestesi Indonesia, 2026)
Cranioplasty is a surgical procedure that restores normal anatomy following craniectomy. Skull bone reconstruction ensures protection and normalizes physiology as well as cerebrospinal fluid dynamics. We present a case of a 37-year-old male following intracerebral hemorrhage (ICH) evacuation via craniotomy. The patient had uncontrolled hypertension and cardiomegaly on chest X-ray, with secondary hemiparesis. Scalp nerve block was employed as an anesthetic technique and for postoperative analgesia. Preoperatively, his heart rate was 70–80 beats/min, blood pressure 158/107 mmHg, and oxygen saturation 100% on room air. Intravenous dexmedetomidine infusion was started (loading dose 1 mcg/kg for 15 minutes, followed by 0.4–0.8 mcg/kg/h) along with 2% lidocaine infusion at 1 mg/kg/h titrated to the desired level of sedation and analgesia. A unilateral (landmark-guided) scalp block was performed using 22 mL of 0.5% levobupivacaine to block the supraorbital, supratrochlear, zygomaticotemporal, auriculotemporal, greater occipital, and lesser occipital nerves. The patient also received intravenous paracetamol 1 g three times daily. Hemodynamics remained stable throughout surgery. The Numeric Rating Scale (NRS) score was 0 at 30 minutes to 6 hours postoperatively, and 1–2 between 8 and 48 hours. Awake regional anesthesia allowed sympathetic tone to remain intact and enabled rapid postoperative neurological assessment. Ultrasound-guided scalp block is an effective alternative anesthetic technique for awake cranioplasty, providing hemodynamic stability, optimal pain control, and faster recovery in high-risk patients